(untitled) (Research, Society and Development, 2020)
The patient presented with the main complaint of "a stain on my gums has appeared". Anamnesis and extraoral physical examination showed no change. In the intraoral physical examination, a dark lesion located in the attached gingiva was observed. An excisional biopsy procedure was proposed to investigate the diagnostic possibility of early oral melanoma. The result of the histopathological examination ruled out the diagnostic hypothesis of the malignant lesion and enabled the definitive diagnosis of the intramucosal oral nevus. The patient has been in follow-up for two years with no signs of recurrence. Pigmented oral lesions have an etiological variety and may also have similar clinical characteristics, especially between oral melanocytic nevi and oral melanoma. Therefore, to obtain a safe diagnosis and, consequently, to establish the most appropriate treatment for these lesions, it is important to make an association between anamnesis and clinical and histopathological examination.